Larvae of the Coral Acropora tenuis (Dana 1846) Settle Under Controlled Light Intensity. (April 2019) - Yusuf, S; Zamani, N P; Jompa, J; Junior, M Z
Abstract: Coral restoration using sexual reproduction could have many advantages over the currently more widely used asexual reproduction methods, in particular for maintaining genetic biodiversity. On-going research on controlled sexual reproduction of corals is seeking ways to achieve higher larval settlement and survival rates. Metamorphic settlement is a critical phase for the survival of coral larvae, due to morphological changes as well as threats of predation and competition. This study aimed to identify the effects of light intensity and substrate positioning on the metamorphosis of competent planula stage larvae. Five day old larvae of the Indo-Pacific coral Acropora tenuis (Dana 1846) were obtained from coral spawning under laboratory conditions. The light intensity experiments used 4 treatments: 170, 130, 90 and 45 μmol.m −2 .s −1 . Substrate positioning experiment treatments were vertical and horizontal orientations of the settlement plates. Coral larval settlement was not significantly correlated with light intensity, despite the higher settlement rates observed under light intensities between 130-170 μmol.m −2 .s −1 . The highest rate of settlement occurred on the ninth day post fertilisation and was significantly higher (α<0.05, df:2) than the rates on day seven and day eleven. The number of coral larvae settling on horizontal substrate was significantly higher compared to vertical plates, with a ratio of 11:1. This understanding of the factors affecting larval metamorphosis and settlement, in particular the importance of light intensity and substrate orientation, could be applied in the on-going efforts to mass produce juvenile corals for coral reef restoration.